Species composition, relative abundance, and distribution of land snail species in Mt. Lantoy Key Biodiversity Area, Cebu, Philippines - RAAMAH ROSALES; EDGARDO LILLO; STEVE MICHAEL ALCAZAR; LEA COLITA; JOED CABALLERO; ARCHIEBALD BALTAZAR MALAKI (Society for Indonesian Biodiversity, 2020)
Abstract. Rosales R, Lillo E, Alcazar SM, Colita L, Caballero J, Malaki AB. 2020. Species composition, relative abundance, and distribution of land snail species in Mt. Lantoy Key Biodiversity Area, Cebu, Philippines. Biodiversitas 21: 5438-5447. This study aimed to establish an inventory of land snails in Mt. Lantoy, Cebu Island, Philippines. A two-person team conducted sampling on eight permanent plots with an elevation range of 182 m-691 m. The study has listed a total of 872 individuals represented by 25 species belonging to 15 genera and nine families. Seven families belong to the air-breathing pulmonate group, Order Stylommatophora: Bradybaenidae, Camaenidae, Trochomorphidae, Achatinidae, Ariophantidae, Helicarionidae, Helicinidae. Two families were under the prosobranch group, Order Caenogastopoda: Cyclophoridae, and Pupinidae. The Cyclophoridae was the richest family with five species, followed by Bradybaenidae, Camaenidae, Helicinidae, having four species. The Trochomorphidae and Helicarionidae have three species. The Pupinidae has two species, while the Achatinidae and Ariophantidae has one species each. There were three (3) endemic and ten (10) new island record species collected and identified with four (4) species that were classified as rare. Rysotta otaheitana Ferussac 1821 was the most abundant, representing 25.22% of the total number of individuals. The Leptoma nitidum ancilis Bartsch 1918 has the widest geographical distribution with a constancy rate of 100%. Widespread species appear to be more abundant, while other species were geographically restricted in few study areas.